Clare Boothe Luce - Nash, Philip, author.
1 online resource.
Keywords: "Clare Boothe Luce: American Renaissance Woman is a concise and highly readable political biography that examines the life of one of the most accomplished American women of the 20th century. Wife and mother, author, editor, playwright, political activist, war journalist, Congresswoman, ambassador, pundit, feminist-Luce did it all. Carefully placing Luce in a series of shifting historical contexts, this book offers the reader an insight into mid-century American political, cultural, gender, and foreign relations history. Eleven primary sources follow the text, including excerpts from Luce's diary, letters, speeches, and published works, as well as a TV talk-show appearance and a critic's diary entry describing an evening with her, helping readers to understand her fascinating life. Together, the narrative and documents afford readers a brief yet in-depth look at Luce with all her complications: glamorous intellectual, acid-tongued diplomat, and feminist conservative, she was a deeply flawed high-achiever who repeatedly challenged the entrenched sexism of her age to become a significant actor in the rise of the "American Century." Addressing the neglect suffered by women in foreign relations history, this will be of interest to students and scholars of US foreign relations, 20th century US history and US women's history"--